Education and Democracy: The Third Way in Karl Mannheim - Canta, Alba Francesca (Italian Sociological Review, 2023)
It is the traumatic events that break the harmony of the world and cause an abrupt turn that devastates all areas of society. Of these, the crisis of democracy and education is one of the harshest: the ability of an individual to actively participate in improving his life and society is in jeopardy. Is there a way forward to build a democratic society? What are the most appropriate methods? What are the main factors that drive this process? These are the questions that K. Mannheim had formulated while witnessing devastating events of his time, and that led him to talk about reconstruction and a new form of democracy, the only form of government capable of putting the individual and the exercise of responsible freedom at the centre (Cesareo & Vaccarini 2009). Mannheim thought it was possible to drive this kind of democratic process through a. democratic planification, which fosters the human development and the participation of all but that, at the same time, guarantees people’s freedom, equality, and dignity; b. democratic education, which represents the main driving factor of this process, capable to form a “new man” which knows how to live in society. The main objective of the essay, is to analyze on a theoretical level Mannheim’s proposal for democracy, highlighting especially the possibility of democratic planning and the importance of education for democracy, describing the steps beyond Mannheim’s analysis. The author thus helps us to understand our Europe today, the problems that afflict it and the possible solutions that contemporary scholars are trying to offer.